2022
DOI: 10.21315/eimj2022.14.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Functional and Non-Functional Distractors and Their Relationship with Difficulty and Discrimination Indices in Four-Option Multiple-Choice Questions

Abstract: Multiple-choice questions-one best answer (MCQ-OBA) is the most frequently accepted assessment tool in Iran’s medical universities. Writing functional distractors (FDs) is an important aspect of framing MCQ-OBA. This study aimed to assess FDs and non-functional distractors (NFDs) in MCQ-OBA and the association of distractor efficiency with difficulty and discrimination indices. This cross-sectional study was conducted at the Department of Immunology, the Ahvaz Jundishapur University of Medical Sciences. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
2
0
3
Order By: Relevance
“…( 4) If DI ≤ 0,19, then the item should be eliminated or completely revised. Lebih lanjut (Botterman et al, 2022;Christian et al, 2017;Date et al, 2019;Kelley, 1939;Kumar Namdeo & Dev Rout, 2016;Masters, 1996;Shakurnia et al, 2022) mengklasifikasikan DI dalam 4 kriteria antara lain: DI ≤ 0,20 (poor), DI 0,21-0,24 (acceptable), DI 0, 25-0,34 (good) and DI ≥ 0,35 (excellent).…”
Section: DImentioning
confidence: 99%
See 3 more Smart Citations
“…( 4) If DI ≤ 0,19, then the item should be eliminated or completely revised. Lebih lanjut (Botterman et al, 2022;Christian et al, 2017;Date et al, 2019;Kelley, 1939;Kumar Namdeo & Dev Rout, 2016;Masters, 1996;Shakurnia et al, 2022) mengklasifikasikan DI dalam 4 kriteria antara lain: DI ≤ 0,20 (poor), DI 0,21-0,24 (acceptable), DI 0, 25-0,34 (good) and DI ≥ 0,35 (excellent).…”
Section: DImentioning
confidence: 99%
“…Menulis Functioning Distractors (FD) adalah aspek penting dalam menyusun pertanyaan pilihan ganda yang berkualitas. Butir soal pilihan ganda dengan distraktor yang efektif sangat penting untuk memperoleh tes yang valid (Shakurnia et al, 2022).…”
Section: Deunclassified
See 2 more Smart Citations
“…A total of 1525 distractor options (62.9%) were functional distractors (FD), and 889 (37%) were non-functional distractors (NFDs). The results showed that the MCQs should be improved (5). Meanwhile, the analysis of the questions of the specialized midwifery courses of the same university was desirable (3).…”
Section: Introductionmentioning
confidence: 99%